CONTRACTUALIST JUSTIFICATION AND THE DIRECTION OF A DUTY. (September 2019) - Jonker, Julian
ABSTRACT: To whom is a duty owed? Contractualism answers with an interest theory of direction. As such, it faces three challenges. The Conceptual Challenge requires acknowledgment that a duty is conceptually distinct from an interest. The Extensional Challenge requires an account of cases in which one who is owed a duty does not take an interest in the duty, or does not take as much of an interest as someone who is not owed the duty. The Positivist Challenge requires explanation of the great flexibility of law and other social practices in positing duties that do not reflect the landscape of moral interests. Contractualism can be shown to meet these challenges once we acknowledge the centrality of the idea of a generic interest. Focusing on generic interests also illuminates the distinctive form of respect involved in directedness.